Remittances and the Economic Crisis : Evidence from the Greenback 2.0 Survey in Italy - Bartolini, Laura; Castagnone, Eleonora (World Bank, Washington, DC, 2015)
Monetary remittances represent the most visible transnational activity of migrants and can be considered as a function of migrant’s ability of producing savings from income and of remitting (supply side), and of the type of claims of family members, either left in the country of origin or residing abroad with the migrant (demand side). Hence, migrant’s remitting capacity is directly linked to the level of economic integration at destination. However, what happens to remittances when the labor market becomes uncertain and the earning potential decreases? Based on a recent survey, this paper explores the effect of the economic crisis on income trends and on the flow of monetary remittances sent to the families left home among three surveyed groups in Turin, Moroccans, Peruvians and Romanians. Results show a widespread worsening of the average economic conditions since the outbreak of the crisis in 2008. The protracted economic instability seems to have effects on migrants’ ability to keep remittance flows constant over time, with differentiated outcomes according to the national groups. While Moroccans show a higher propensity in receiving remittances, Peruvians are those who resist more to a remittance drop over the last five years. Beyond economic determinants, observed patterns in remittance trends can also be explained by migrant household characteristics in Italy and abroad and to unobserved variables (distance) related to the country of origin.